Normal weight obesity is associated with lower AFC and adverse IVF outcomes - Yao, Yangcheng; Liu, Wenjuan; Zhang, Xiqian; Su, Nianjun; Huang, Li; Nong, Yingqi; Xiao, Xiaomin; Liu, Fenghua (Frontiers in Endocrinology, 2024)
Body weight could be classified into underweight, normal weight and overweight according to percentage of body fat (%BF), and normal weight obesity (NWO) is defined as a normal BMI but a high %BF. While the impact of NWO in women fecundity remain unknow.Therefore, this study aimed to investigate the associations between %BF and reproductive outcomes among in vitro fertilization (IVF) women with normal BMI. A total of 469 women were included in this study and were classified into low %BF, normal %BF and high %BF according to previous study. Multivariate generalized regression models were employed to evaluate the associations of %BF with ovarian reserve parameters, IVF outcomes and early pregnancy outcomes. We further run sensitivity analyses by restricted the analysis to young women and those only with tubal factor, respectively. About 32.2% of normal BMI women were misclassified according %BF, with 16.4% of them were low %BF and 15.8% were high %BF. The high %BF group had significantly lower antral follicle count (AFC) than normal %BF groups, and the AFC showed a tendency of decrease as %BF increased. In sensitivity analysis in young women, high %BF group also had significantly lower number of good-quality embryos when compared to normal %BF groups. The results expanded to all IVF outcomes when analysis restricted to tubal factor women. In summary, misclassifications of body weight status based on BMI are common according to %BF, and NWO is associated with adverse reproductive outcomes.